Assessment of motorcycle as a means of transportation system and crime activities in Ore, Ondo State, Nigeria (International Journal of Sustainable Development & World Policy, 2025)
Motorcycles have become an alternative to conventional means of transportation such as tricycles, buses, and minibuses in most developing countries of the Saharan Africa sub-region. This study therefore examined the effects of motorcycles as an alternative transportation system and their association with crime activities in Ore, Ondo State. A mixed sampling technique was adopted for this study. Motorcyclists' parks in the area were stratified into eight units that were purposively selected, from which 150 respondents were randomly sampled. Descriptive statistics (charts, tables of percentages, and Mean Weight Value) were used to analyze respondents' bio-data, causes, types, and effects of crime on commuters by the cyclists, while inferential statistics (Chi-square) were used to analyze the stated hypotheses. The research revealed that greed for material things, security lapses, and other factors were causes of crimes. Types of crimes included physical injury infliction, murder, robbery, assault, and rape. The effects of crimes on commuters included physical injuries, loss of valuables, and psychological disorders, among others. The results of the hypothesis test at a 5% level of significance showed that since the calculated X2 value of 88.08 was greater than the table value of 8.34, the null hypothesis was rejected in favor of the alternative hypothesis, indicating that socio-economic factors of the respondents influence crime activities in Ore. The study concluded that most crimes in the area are committed by commercial motorcyclists. The study recommended that intelligence and surveillance operations should be intensified within the neighborhood to curb these activities.